2018
DOI: 10.1016/j.cmet.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gut Microbiota Remodeling Contributes to the Caloric Restriction-Induced Metabolic Improvements

Abstract: Caloric restriction (CR) stimulates development of functional beige fat and extends healthy lifespan. Here we show that compositional and functional changes in the gut microbiota contribute to a number of CR-induced metabolic improvements and promote fat browning. Mechanistically, these effects are linked to a lower expression of the key bacterial enzymes necessary for the lipid A biosynthesis, a critical lipopolysaccharide (LPS) building component. The decreased LPS dictates the tone of the innate immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(166 citation statements)
references
References 62 publications
(82 reference statements)
11
154
0
1
Order By: Relevance
“…Loss of appetite is also reported after human influenza virus and RSV infection (Monto et al, 2000;Widmer et al, 2012). Reduced calorie intake in humans and mice has been associated with a significant increase in the ratio of Bacteroidetes to Firmicutes abundance (Ley et al, 2006;Fabbiano et al, 2018;Wang et al, 2018), similar to that observed in our prior viral infection study. This suggests that changes in the gut microbiota seen after respiratory viral infection might be driven by reduced food intake.…”
Section: Introductionsupporting
confidence: 82%
“…Loss of appetite is also reported after human influenza virus and RSV infection (Monto et al, 2000;Widmer et al, 2012). Reduced calorie intake in humans and mice has been associated with a significant increase in the ratio of Bacteroidetes to Firmicutes abundance (Ley et al, 2006;Fabbiano et al, 2018;Wang et al, 2018), similar to that observed in our prior viral infection study. This suggests that changes in the gut microbiota seen after respiratory viral infection might be driven by reduced food intake.…”
Section: Introductionsupporting
confidence: 82%
“…Candidate mechanisms could involve tissueautonomous and tissue-independent processes. For instance, DR remodels the gut microbiome, which causally contributes to metabolic reprogramming in liver and WAT 44,45 . Loss of DR-essential microbiome species during ageing under AL feeding could thus render mice refractory to late-onset DR.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota influences fatty acid oxidation, lipogenesis, satiety, and metabolic endotoxemia. Effects of gut bacteria on risk for CVD, and T2D is inconsistent, and these effects are mediated via metabolites such as short‐chain fatty acids (SCFAs), secondary bile acids, LPS, and trimethylamine (TMA) . Of these, TMA produced by gut bacteria through choline, phosphatidylcholine, and l ‐carnitine can be oxidized to TMA N‐oxide (TMAO).…”
Section: Impact Of Gut Microbiota On Obesity and Inflammationmentioning
confidence: 99%